Characterization of Maize Acetyl-Coenzyme A Carboxylase. - Egli, M. A. (1993)
Maize (Zea mays L.) leaf acetyl-CoA carboxylase (ACCase) was purified about 500-fold by ammonium sulfate fractionation and gel filtration and blue Sepharose affinity and anion-exchange chromatography. Most ACCase activity (85%) recovered from the anion-exchange column was found in a highly purified fraction (specific activity 5.5 [mu]mol acid-stable product min-1 mg-1) that consisted primarily of a single 227-kD biotinylated polypeptide. The fraction represented 29% of the original activity and was designated ACCase I. A second partially purified ACCase activity (ACCase II) eluted earlier during anion-exchange chromatography, contained a single biotinylated polypeptide of 219 kD, was poorly recognized by antiserum raised against the ACCase I polypeptide, and was less inhibited by the herbicides haloxyfop or sethoxydim than was ACCase I. ACCase I and II both utilized propionyl-CoA as substrate about 50% as effectively as acetyl-CoA, and neither utilized methylcrotonyl-CoA. Immunoprecipitation with antiserum and protein blotting of crude extracts of leaf, embryo, and endosperm tissue and suspension cells indicated that most ACCase activity in these tissues was immunologically similar and consisted of ACCase I. Only leaves contained significant amounts of the ACCase II polypeptide; however, no ACCase II polypeptide was found in isolated mesophyll chloroplasts. The ACCase I and II polypeptides appear to be subunits of distinct ACCase isoforms.